A normal electrocardiogram precludes the need for left ventriculography in the assessment of coronary artery disease - Khan, M (1998)
Objective—To assess whether a normal electrocardiogram can identify good left ventricular function and obviate the need for routine left ventriculography in patients undergoing cardiac catheterisation for suspected coronary artery disease. Design—A prospective study of patients undergoing cardiac catheterisation. Setting—A regional cardiac centre. Patients—The electrocardiograms, coronary angiograms, and left ventriculograms of 391 consecutive patients undergoing investigations for suspected coronary artery disease were entered into the study. Patients with arrhythmias and cardiac pathologies other than coronary artery disease were excluded. Main outcome measures—The electrocardiogram was assessed using a 29 point QRS scoring system, and classified by two cardiologists and a trainee cardiologist as normal or abnormal. Left ventricular function was assessed by digital ventriculography. Results—The sensitivity, specificity, and negative predictive value of a QRS score of 0 (normal QRS complexes) for discriminating good left ventricular function (ejection fraction ⩾ 50%) were 92.6%, 41.5%, and 97.2%, respectively. The figures for a normal electrocardiogram as assessed by a doctor were 96.3%, 40.4%, and 98.6% for cardiologist A; 96.3%, 37.4%, and 98.4% for cardiologist B; and 94.4%, 49.6%, and 98.2% for the cardiology trainee. Conclusions—If a cardiologist judges the ECG to be normal, left ventriculography is unnecessary and a formal QRS score does not improve reliability of this clinical judgment. Adopting this strategy would save £30-40 000 in consumables and 65-87 hours of catheter laboratory and staff time for a department catheterising 3000( )patients with suspected coronary artery disease annually.   Keywords: cardiac catheterisation;  electrocardiogram;  left ventricular ejection fraction